2017
DOI: 10.1371/journal.pone.0170634
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tumor-infiltrating lymphocytes (TILs) to predict the treatment response to eribulin chemotherapy in breast cancer

Abstract: BackgroundEribulin mesylate (eribulin) is currently indicated for treatment of locally advanced or metastatic breast cancer (MBC). It is a cytotoxic agent with unique mechanisms that suppress epithelial-mesenchymal transition (EMT) of cancer cells. On the other hand, Tumor-infiltrating lymphocytes (TILs), which are considered indicators of immune response monitoring, have been reported as prognostic factors and predictors of therapeutic efficacy. We thought that eribulin, which has an EMT-inhibiting mechanism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 33 publications
1
79
0
Order By: Relevance
“…In this manner, EMT also ANTICANCER RESEARCH 38: 2929-2938(2018 2934 regulated immune functions in tumor tissues. We have previously reported that the number of tumor-infiltrating lymphocytes is a predictive marker for eribulin-responders (33). Our updated results indicate that eribulin accelerated the anti-tumor immune response and also showed efficacy in patients with metastatic breast cancer.…”
Section: Discussionsupporting
confidence: 51%
“…In this manner, EMT also ANTICANCER RESEARCH 38: 2929-2938(2018 2934 regulated immune functions in tumor tissues. We have previously reported that the number of tumor-infiltrating lymphocytes is a predictive marker for eribulin-responders (33). Our updated results indicate that eribulin accelerated the anti-tumor immune response and also showed efficacy in patients with metastatic breast cancer.…”
Section: Discussionsupporting
confidence: 51%
“…Although no significant difference in OS was observed between groups with high and low ALC (c; p = 0.287), those with NLR ≥5.0 had significantly worse OS than those with NLR < 5.0 (d; p < 0.001). antitumor immunity [7,8], while the number of tumorinfiltrating lymphocytes has been known to affect the efficacy of eribulin treatment for breast cancer [23]. Given the difficulty in determining the number of tumor-infiltrating lymphocytes in daily practice, we propose the use of ALC as a predictive marker of the efficacy of eribulin, considering that a significant correlation between tumor-infiltrating lymphocytes and ALC has been already confirmed [18].…”
Section: Discussionmentioning
confidence: 96%
“…Eribulin presents a unique opportunity to investigate a compound that has a number of beneficial nonmitotic properties, in addition to its potent antimitotic properties, as an ADC payload. Eribulin has been shown to inhibit epithelial-to-mesenchymal transition (EMT), which has been associated with a more immunosuppressive tumor microenvironment (19,20), and enhance infiltration of tumor-infiltrating lymphocytes (47). In addition, eribulin also increases vascular perfusion in tumors and reduces hypoxia.…”
Section: Discussionmentioning
confidence: 99%